Occurrence of hepatitis E virus infection in acute hepatitis in Thailand. Issue 10 (2nd July 2014) - Siripanyaphinyo, U.; Boon‐Long, J.; Louisirirotchanakul, S.; Takeda, N.; Chanmanee, T.; Srimee, B.; Namsai, A.; Pounsawat, P.; Khupulsap, K.
Abstract Hepatitis E virus (HEV) infection is one of the enterically transmitted types of hepatitis. The present study was undertaken to estimate the occurrence of HEV infection in sporadic acute hepatitis in Thailand. Serum samples were obtained from 614 suspected acute hepatitis patients at two large hospitals in Bangkok during 2008, 2009, and 2011. Acute hepatitis E was identified by the presence of anti‐HEV IgM (4.8%) using indirect ELISA kits and/or HEV RNA (4.5%) by a semi‐nested reverse transcription‐polymerase chain reaction assay. HEV IgM was the most common marker for detection (77%) at diagnosis, either by positive HEV IgM alone or together with HEV RNA, whereas HEV RNA alone was detected in 23% of patients. Overall, 4.2% of cases (26 out of 614) were acute HEV infection with the highest attack rate in the elderly age group. In addition, nucleotide sequence analysis of five HEV samples revealed 92.8–99.8% homology. All viruses were clustered into HEV genotype 3 and were similar genetically to swine HEV strains previously detected in the same area. Therefore, the occurrence of HEV infection with closely related to swine genotype 3 was approximately 4–5% of acute hepatitis cases in Thailand. Anti‐HEV IgM was the most common marker at diagnosis. J. Med. Virol. 86: 1730–1735, 2014. © 2014 Wiley Periodicals, Inc.